Bentuk-bentuk Akronim yang Digunakan di Unit Pelaksana Teknis Dinas (UPTD) Balai Peralatan dan Perbekalan Dinas Pekerjaan Umum Provinsi Sulawesi Utara - Loindong, Pamela; Bachmid, Gayda; Imbang, Djeinnie (Universitas Sam Ratulangi, 2017)
Language is a means of human communication through social interaction with others. According to Chomsky, language is a collection of sentences, each with a certain length and built by a set of specific elements. Language is a regular system from various forms of sounds used in expressing thoughts and feelings of the users of the language. Indonesian language was born on October 28, 1928, grew and developed from the Malay language since ancient times, and has been used as a lingua franca not only in the archipelago, but also in almost all of Southeast Asia. This study examines the language based on the internal object of linguistic study; micro linguistic and one of its sub-discipline is morphology, focused on forms of acronyms used in UPTD Balai Peralatan dan Perbekalan Dinas Pekerjaan Umum Provinsi Sulawesi Utara. The research focus is on the forms of acronyms used in UPTD Balai Peralatan dan Perbekalan Dinas Pekerjaan Umum Provinsi Sulawesi Utara. There are three forms of acronyms used by the Aparatur Sipil Negera (Civil Servant) and Tenaga Harian Lepas (Intern) on UPTD Balai Peralatan dan Perbekalan Dinas Pekerjaan Umum Provinsi Sulawesi Utara, which is acronym whose form is determined by the formation process based on the theory of O'Grady, Dobrovolsky, theory of Kridalaksana. H., and one of the form does not follow the two existing theories. Of the thirty two acronyms found, twenty nine are formal acronyms in Indonesian language and the other three are informal acronyms.Â Â